Pengaruh Jarak Tanam dan Pemberian Mulsa Organik terhadap Pertumbuhan dan Produksi Tanaman Kacang Hijau (Vigna radiata L.) - Yoggi Arianjaya; Adiwirman Adiwirman; Isna Rahma Dini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the effect of spacing and administration of sawdust organic mulch and to get the best combination in increasing the growth and production of green bean (Vignaradiata L.). This research was carried out at the University of Riau Faculty of Agriculturefor four months from April to July 2018. The research was conducted experimentally in a 2 x 4 factorial form arranged according to the Randomized Block Design (RBD). The first factor isspacing consists of three levels: 40 cm x 20 cm, 40 cm x 15 cm and 40 cm x 10 cm. The second factor is sawdust mulch consisting of two levels: Without sawdust organic mulch and 4 kg.2m-2 sawdust organic mulch. The parameters observed were plant height, number of primary branches, stem diameter, flowering age, canopy area, number of plant pods, number of planted pods, plot production and weight of 100 seeds. Spacing can increase plant height, number of primary branches and stem diameter of green bean plants. Sawdust mulch had no effect on the parameters of plant height, number of primary branches, stem diameter, flowering age, canopy area, number of plant pods, number of rice pods, plot production and weight of 100 seeds of green bean plants. Keywords: spacing, organic mulch, green bean